Role of e-FAST in patients presenting with blunt injury abdomen and thorax and their correlation with operative or conservative management - Tripura, Rathindra; Mittal, Gyanendra S.; Singh, Rajdeep; Kshirsagar , Mrunal B. (International Surgery Journal, 2025)
Background: This study aims to explore the role of e-FAST in patients with blunt abdominal and thoracic trauma, evaluating its accuracy in guiding management decisions and its correlation with operative versus conservative treatment approaches, ultimately seeking to improve triage efficiency, reduce delays in treatment and enhance patient outcomes in trauma care. Methods: Prospective study was conducted in General Surgery Emergency Department, Rama Medical College Hospital and Research centre, Hapur, U.P from June 2022–June 2024. E-FAST in blunt trauma abdomen patients. Patients above the age of 12 years. All patients with blunt abdominal trauma and blunt chest trauma. Pregnant patients were included. Patients with penetrating injuries. Psychiatric patients and Paediatric patients (below 12 years of age) were excluded. Number of groups were 3. Blunt abdominal trauma patients (above 12 years). blunt chest trauma patients (above 12 years). pregnant patients (with blunt abdominal or chest trauma). Results: The prospective observational study was conducted at Emergency Department, Rama Medical College, Hospital and Research centre, Hapur, U.P. Sixty patients above the age of twelve were taken as study sample. The main goal of this study is to offer valuable insights into the efficacy of e-FAST ultrasound as a crucial imaging tool. This is vital for supporting clinical practice with empirical evidence and determining the optimal significance to attribute to these scans in guiding the management of acutely injured patients. Conclusions: In conclusion, the study reaffirms the role of e-FAST as a frontline diagnostic tool in blunt trauma management.